Transparent conductive piezoelectric laminate film

JP7629986B2Active Publication Date: 2025-02-14KUREHA CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023514600
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-15
Filing Date
2022-03-30
Publication Date
2025-02-14
Estimated Expiration
2042-03-30

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、高い透明性及び低抵抗を実現する透明導電性圧電積層フィルムを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629986000002
    Figure 0007629986000002
  • Figure 0007629986000003
    Figure 0007629986000003
  • Figure 0007629986000004
    Figure 0007629986000004
Patent Text Reader

Abstract

Provided is a transparent conductive piezoelectric laminated film that realizes high transparency and low resistance. The present invention is related to a transparent conductive piezoelectric laminated film comprising a piezoelectric film, and a conductor layer laminated on at least one surface of the piezoelectric film, said transparent conductive piezoelectric laminated film having diffraction peaks in each of the 21°±2° range and the 31°±2° range in X-ray diffraction measurement and having a haze value of 2.0% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive piezoelectric laminate film and a device including the same. [Background technology]

[0002] Touch panels are widely used as devices that allow users to input information by directly touching an image display unit. A representative type of touch panel is a capacitive touch panel that utilizes the change in current capacity that occurs between a transparent electrode and a finger (Patent Document 1).

[0003] Transparent conductive films are used in the position detection sensors used in touch panels; for example, a film of ITO (indium tin oxide) is formed on a PET film, and then the crystallinity of the ITO is increased by heat treatment (at around 150°C), thereby achieving low resistance and high transmittance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-324203 Summary of the Invention [Problem to be solved by the invention]

[0005] Recently, attention has been focused on technology that can simultaneously detect the position and pressure when an operation surface is touched by a finger or other object, and it has been proposed to achieve this by combining it with a pressure detection sensor made of a piezoelectric sensor.

[0006] However, the transparent conductive piezoelectric film used in piezoelectric sensors is difficult to use in touch panels because, like PET film, its resistance deteriorates and its color is damaged when it is subjected to high-temperature heat treatment.

[0007] The present invention has been made in view of the above problems, and has an object to provide a transparent conductive piezoelectric laminate film that achieves high transparency and low resistance. [Means for solving the problem]

[0008] The present inventors have found that the above-mentioned problems can be solved by a transparent conductive piezoelectric laminate film that includes a piezoelectric film and a conductive layer laminated on at least one surface of the piezoelectric film and has a specific diffraction peak and haze value, and have completed the present invention.

[0009] The present invention relates to a transparent conductive piezoelectric laminate film comprising a piezoelectric film and a conductive layer laminated on at least one surface of the piezoelectric film, which has diffraction peaks in the range of 21°±2° and in the range of 31°±2° in X-ray diffraction measurement, and has a haze value of 2.0% or less.

[0010] The conductive layer preferably contains indium or an indium compound, and a metal other than indium and tin or a compound of such a metal.

[0011] It is preferable that the diffraction intensities of the diffraction peaks in the range of 21°±2° and the range of 31°±2° are both 100 cps or more.

[0012] The transparent conductive piezoelectric laminate film preferably has a surface resistance of 200 Ω / sq or less as measured from the conductive layer side.

[0013] The piezoelectric film preferably contains a fluorine-based resin.

[0014] It is preferable that the piezoelectric film further includes a transparent coating layer on the surface facing the conductive layer.

[0015] The present invention also relates to a device comprising the transparent conductive piezoelectric laminate film.

[0016] The present invention also relates to a method for producing the above-mentioned transparent conductive piezoelectric laminate film, comprising: (A) a step of forming a conductive layer on at least one surface of a transparent piezoelectric film containing a fluorine-based resin to obtain a laminate film; and (B) a step of annealing the laminate film obtained in the above step (A) at 85 to 130°C.

[0017] In the above step (A), before forming the conductive layer, it is preferable to form a transparent coating layer on the surface of the transparent piezoelectric film on which the conductive layer is to be formed, and then form the conductive layer on the transparent coating layer. Effect of the Invention

[0018] According to the present invention, a transparent conductive piezoelectric laminate film that realizes high transparency and low resistance can be provided. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view illustrating a schematic diagram of one embodiment of a transparent conductive piezoelectric laminate film of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of another embodiment of the transparent conductive piezoelectric laminate film of the present invention. [Diagram 3] 1 shows the results of X-ray diffraction measurement in Example 1. [Figure 4] 1 shows the results of X-ray diffraction measurement in Example 2. [Diagram 5] 1 shows the results of X-ray diffraction measurement of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings. However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0021] <Transparent conductive piezoelectric laminate film> The transparent conductive piezoelectric laminate film of the present invention comprises a piezoelectric film and a conductive layer laminated on at least one surface of the piezoelectric film, and in X-ray diffraction measurement, has diffraction peaks in the range of 21°±2° and in the range of 31°±2°, and has a haze value of 2.0% or less.

[0022] In this specification, the term "laminated" means that each layer is laminated in order, and other layers may be laminated between each layer.

[0023] <Characteristics of transparent conductive piezoelectric laminate film> In X-ray diffraction measurement, the transparent conductive piezoelectric laminate film has diffraction peaks in the range of 21°±2° and in the range of 31°±2°. Due to these characteristics, a transparent conductive piezoelectric laminate film that achieves high transparency and low resistance can be provided. In this specification, the X-ray diffraction measurement is performed by an in-plane method. In addition, in this specification, "having a diffraction peak in the range of 21°±2°" means that the diffraction intensity (I 17 ) and the diffraction intensity at a diffraction angle (2θ) of 25° (I 25 ) is set as the baseline, the baseline diffraction intensity (I 17 and I 25 The diffraction intensity at a diffraction angle (2θ) of 27° is defined as the average value of the diffraction intensity at a diffraction angle (2θ) of 27° and the diffraction intensity at a diffraction angle (2θ) of 27°. 27 ) and the diffraction intensity (I 35 ) is set as the baseline, the baseline diffraction intensity (I 27 and I 35 This means that a mountain-shaped portion with a diffraction intensity two or more times (preferably three or more times) the diffraction intensity of the sample is observed in the range of 31°±2°. The method for obtaining the above-mentioned characteristics is not particularly limited, but may be, for example, forming a conductive layer containing a metal other than indium and tin or a compound of such a metal, and performing a specified annealing treatment. The diffraction intensity of the diffraction peak in the range of 21°±2° is preferably 100 cps or more, more preferably 150 cps or more, and even more preferably 250 cps or more. The diffraction intensity of the diffraction peak in the range of 31°±2° is preferably 100 cps or more. Furthermore, it is preferable that all of the diffraction intensities are 100 cps or more.

[0024] The haze value of the transparent conductive piezoelectric laminate film is 2.0% or less, preferably 1.5% or less, and more preferably 1.0% or less. The lower limit of the haze value is not particularly limited, but is, for example, 0.1%. In this specification, the haze value is measured in accordance with JIS K 7136.

[0025] The surface resistance of the transparent conductive piezoelectric laminate film measured from the conductive layer side is preferably 200 Ω / sq or less, more preferably 170 Ω / sq or less. The lower limit of the surface resistance is not particularly limited, but is, for example, 5 Ω / sq. In this specification, the surface resistance is measured in accordance with JIS K 7194.

[0026] The transparent conductive piezoelectric laminate film preferably has a total light transmittance of 80% or more. The upper limit of the total light transmittance is not particularly limited, but is, for example, 95%. In this specification, the total light transmittance is measured in accordance with JIS K 7361-1.

[0027] L of transparent conductive piezoelectric laminate film * is preferably 80 or more, and more preferably 90 or more. * The upper limit is not particularly limited. Transparent conductive piezoelectric laminate film a * is preferably −3 to 3, and more preferably −2 to 2. Transparent conductive piezoelectric laminate film b * is preferably −5 to 5. In this specification, L * a * b * The above L in the color system * , a * , and b * is measured in accordance with JIS Z 8722.

[0028] The thickness of the transparent conductive piezoelectric laminate film is preferably 5 to 200 μm, more preferably 20 to 100 μm. When the thickness is 5 μm or more, the mechanical strength tends to be sufficient. When the thickness is 200 μm or less, the transparency tends to be sufficient, so that the film can be easily used for optical purposes.

[0029] Next, each layer of the transparent conductive laminated film will be described with reference to the drawings.

[0030] 1 is a cross-sectional view showing a schematic diagram of one embodiment of a transparent conductive piezoelectric laminate film. A transparent conductive piezoelectric laminate film 1 has a piezoelectric film 11 and a conductive layer 31 laminated on one surface of the piezoelectric film 11. 2 is a cross-sectional view that illustrates a schematic diagram of another embodiment of the transparent conductive piezoelectric laminate film of the present invention. The transparent conductive piezoelectric laminate film 2 differs from the transparent conductive piezoelectric laminate film 1 in that a transparent coating layer (first transparent coating layer 21) is provided on the surface of the piezoelectric film 11 that faces the conductor layer 31 of the piezoelectric film 11. The other configurations are the same as those of the transparent conductive piezoelectric laminate film 1.

[0031] <Piezoelectric film> The piezoelectric film 11 is a transparent film (thin film) having piezoelectricity (the property of converting an applied force into a voltage, or the property of converting an applied voltage into a force).

[0032] Examples of the piezoelectric film 11 include fluororesins, vinylidene cyanide polymers, odd-numbered nylons such as nylon 9 and nylon 11, helical chiral polymers such as polylactic acid, polyhydroxycarboxylic acids such as polyhydroxybutyrate, cellulose derivatives, and polyurea. Examples of fluorine-based resins include polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers (e.g., vinylidene fluoride / trifluoroethylene copolymer, vinylidene fluoride / trifluoroethylene / chlorotrifluoroethylene copolymer, hexafluoropropylene / vinylidene fluoride copolymer, perfluorovinyl ether / vinylidene fluoride copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, hexafluoropropylene oxide / vinylidene fluoride copolymer, hexafluoropropylene oxide / tetrafluoroethylene / vinylidene fluoride copolymer, hexafluoropropylene / tetrafluoroethylene / vinylidene fluoride copolymer); tetrafluoroethylene polymers; chlorotrifluoroethylene polymers; and the like. These can be used alone or in combination of two or more. Among these, from the viewpoints of the high piezoelectricity obtained, weather resistance, heat resistance, and the like, fluororesins are preferred, and polyvinylidene fluoride and / or vinylidene fluoride copolymers are more preferred.

[0033] The piezoelectric film 11 may further contain commonly used additives (such as a filler or a surfactant).

[0034] The thickness of the piezoelectric film 11 is preferably 5 to 200 μm, and more preferably 20 to 100 μm. If it is 5 μm or more, the mechanical strength tends to be sufficient. If it is 200 μm or less, the transparency tends to be sufficient, and therefore it tends to be easy to use for optical purposes.

[0035] <Conductive layer> The conductive layer 31 is a transparent layer that exhibits electrical conductivity. The conductive layer 31 preferably contains indium or an indium compound, and a metal other than indium and tin or a compound of the metal, which makes it easy to increase the crystallinity of the conductive layer even with a relatively low-temperature heat treatment, and therefore tends to prevent the performance of the piezoelectric film from deteriorating, and to achieve high transparency and low resistance.

[0036] Examples of indium compounds include indium oxides such as indium tin oxide (ITO), indium oxide, and indium zinc oxide. These can be used alone or in combination of two or more. Among these, indium oxide is preferred. Examples of metals other than indium and tin include zirconium, scandium, yttrium, tantalum, and hafnium. Examples of compounds of these metals include metal oxides such as zirconium oxide, scandium oxide, yttrium oxide, tantalum oxide, and hafnium oxide. These can be used alone or in combination of two or more. Among these, tantalum oxide and / or hafnium oxide are preferred.

[0037] It is preferable that the conductive layer 31 does not contain tin or a tin compound. This makes it easier to increase the crystallinity of the conductive layer 31 even with a heat treatment at a relatively low temperature, which tends to prevent the performance of the piezoelectric film from deteriorating and to achieve high transparency and low resistance.

[0038] The conductive layer 31 may contain trace components or unavoidable components to the extent that the functions of the conductive layer 31 are not impaired.

[0039] The thickness of the conductive layer 31 is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. The thickness is preferably 55 nm or less, and more preferably 40 nm or less. When the thickness is 10 nm or more, the surface resistance value is 1×10 3 A continuous coating having good electrical conductivity of Ω / sq or less tends to be obtained. When the thickness is 55 nm or less, good transparency tends to be obtained.

[0040] A wiring electrode or the like may be provided on the conductive layer 31. A current passing through the conductive layer 31 is guided to the wiring electrode or the like provided on the conductive layer 31.

[0041] <Transparent coating layer> The transparent conductive piezoelectric laminate film 2 includes a first transparent coating layer 21 on the surface of the piezoelectric film 11 that faces the conductive layer 31 of the piezoelectric film 11. That is, the transparent conductive piezoelectric laminate film 2 has a laminated structure in which the piezoelectric film 11, the first transparent coating layer 21, and the conductive layer 31 are laminated in this order. Furthermore, the transparent conductive piezoelectric laminate film 2 may also be provided with a second transparent coating layer on the surface of the piezoelectric film 11 opposite to the conductive layer 31 side of the piezoelectric film 11. In this case, the transparent conductive piezoelectric laminate film has a laminated structure in which the second transparent coating layer, the piezoelectric film 11, the first transparent coating layer 21, and the conductive layer 31 are laminated in this order. The thickness, structure, and composition of the first transparent coating layer 21 and the second transparent coating layer may be the same or different. Alternatively, the transparent conductive piezoelectric laminate film may only have the second transparent coating layer.

[0042] Examples of the transparent coating layer include a hard coat layer, an optical adjustment layer, and an undercoat layer. The transparent coating layer may be a single layer of these, or a combination of multiple layers. By providing a transparent coating layer, it is easy to suppress scratches occurring in the transparent conductive piezoelectric laminate film 2 and to improve the transparency of the transparent conductive piezoelectric laminate film 2. Furthermore, although the annealing treatment may cause thermal shrinkage of the film, making it difficult to obtain low resistance, by providing a transparent coating layer, thermal shrinkage is suppressed and low resistance can be easily obtained.

[0043] The transparent coating layer contains, for example, a resin cured product obtained by curing a resin composition. The resin composition preferably contains at least one selected from a thermosetting resin composition, an ultraviolet-curable resin composition, and an electron beam-curable resin composition. The resin composition may contain at least one selected from a (meth)acrylic acid ester resin, a urethane resin, an epoxy-based resin, a phenoxy-based resin, and a melamine-based resin.

[0044] The resin composition is a composition containing a curable compound having an energy ray reactive group such as a (meth)acryloyl group or a vinyl group. The expression "(meth)acryloyl group" means that it includes at least one of an acryloyl group and a methacryloyl group. The curable compound preferably contains a multifunctional monomer or oligomer containing two or more, preferably three or more, energy ray reactive groups in one molecule. When a resin composition that can be cured by energy rays is used, the resin composition can be cured by irradiating it with energy rays such as ultraviolet rays, etc. Therefore, the use of such a resin composition is preferable from the viewpoint of the manufacturing process.

[0045] The curable compound preferably contains an acrylic monomer, such as a urethane-modified acrylate or an epoxy-modified acrylate.

[0046] The resin composition preferably contains organic fine particles and / or inorganic fine particles from the viewpoints of increasing the strength of the coating film, adjusting the refractive index, increasing the transparency of the transparent conductive piezoelectric laminate film, etc. In particular, it is more preferable that the resin composition contains inorganic fine particles from the viewpoint of adhesion between the transparent coating layer and the conductive layer. Examples of the organic fine particles include organic silicon fine particles, crosslinked acrylic fine particles, and crosslinked polystyrene fine particles. Examples of the inorganic fine particles include synthetic silica particles, talc particles, diatomaceous earth particles, calcium carbonate particles, feldspar particles, quartz particles, aluminum oxide fine particles, zirconium oxide fine particles, titanium oxide fine particles, and iron oxide fine particles.

[0047] The average particle size of the fine particles may be 100 nm or less from the viewpoint of ensuring sufficient transparency and being smaller than the thickness of the transparent coating layer. On the other hand, from the viewpoint of producing a colloidal solution, it may be 5 nm or more, or 10 nm or more. When organic fine particles and / or inorganic fine particles are used, the total amount of the organic fine particles and inorganic fine particles may be, for example, 5 to 500 parts by mass, or 20 to 200 parts by mass, relative to 100 parts by mass of the curable compound. In this specification, the average particle size refers to the cumulative average particle size (D50) on a volume basis measured by scanning electron microscopy (SEM).

[0048] If the transparent coating layer is too thin, the transparent coating layer may not be able to sufficiently cover the fine unevenness on the surface of the piezoelectric film, and the effect of reducing the haze of the piezoelectric film may not be sufficiently obtained. Also, if the transparent coating layer is too thick, the piezoelectricity of the transparent conductive piezoelectric laminate film may be insufficient. Therefore, the thicknesses of the first transparent coating layer 21 and the second transparent coating layer are preferably 0.20 μm or more, more preferably 0.35 μm or more, and even more preferably 0.50 μm or more, from the viewpoint of reducing the haze of the piezoelectric film. Also, the thickness of the transparent coating layer is preferably 3.5 μm or less, more preferably 2.5 μm or less, and even more preferably 1.5 μm or less, from the viewpoint of obtaining a transparent conductive piezoelectric laminate film that can fully express the piezoelectric properties of the piezoelectric film. By having the thickness of the transparent coating layer in the above range, it is possible to achieve both sufficient piezoelectricity and transparency according to the application in the transparent conductive piezoelectric laminate film.

[0049] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments. For example, the transparent conductive piezoelectric laminate film 2 described above has only the first transparent coating layer 21, but it may have both the first transparent coating layer 21 and the second transparent coating layer, or it may have only the second transparent coating layer.

[0050] <Applications of transparent conductive piezoelectric laminated film> The transparent conductive piezoelectric laminate film according to the present invention is suitably used in devices such as capacitive and resistive touch panels. The device further includes a general display panel unit, such as an LCD, under the transparent conductive piezoelectric laminate film. The above device is suitable for use as a display device for mobile phones, smartphones, personal digital assistants, tablet PCs, notebook computers, sales equipment, ATMs, factory automation equipment, office automation equipment, medical equipment, car navigation systems, and the like.

[0051] <Method for manufacturing transparent conductive piezoelectric laminate film> The transparent conductive piezoelectric laminate film of the present invention can be produced, for example, by forming a transparent coating layer, if necessary, on at least one surface of a piezoelectric film, forming a conductive layer, and then performing an annealing treatment.

[0052] <Method of forming transparent coating layer> The first transparent coating layer can be prepared by applying a solution or dispersion of the resin composition to one side of the piezoelectric film, drying the solution or dispersion, and curing the resin composition. The application can be performed by a known method. Examples of the application method include an extrusion nozzle method, a blade method, a knife method, a bar coat method, a kiss coat method, a kiss reverse method, a gravure roll method, a dip method, a reverse roll method, a direct roll method, a curtain method, and a squeeze method. The second transparent coating layer can also be prepared on the other side of the piezoelectric film in the same manner as the first transparent coating layer.

[0053] <Method of forming conductive layer> The conductive layer can be formed by a vacuum deposition method such as a vacuum deposition method, a sputtering method, an ion plating method, or a CVD method. Among these, the sputtering method is preferred because it can reduce the size of the deposition chamber and has a high deposition rate. As the target, a metal target, a metal compound target, or the like can be used.

[0054] In the sputtering method, the sputtering gas may be, for example, an inert gas such as Ar. If necessary, a reactive gas such as oxygen gas may be used in combination. When a reactive gas is used in combination, the flow rate of the reactive gas is not particularly limited, but is, for example, 0.1% or more and 5% or less with respect to the total flow rate of the sputtering gas and the reactive gas. The air pressure during sputtering is, for example, 1 Pa or less, and preferably 0.7 Pa or less, from the viewpoints of suppressing a decrease in the sputtering rate, discharging stability, and the like. The power source used in the sputtering method may be, for example, any of a DC power source, an AC power source, an MF power source, and an RF power source, or a combination of these. The temperature during sputtering is not particularly limited, but from the viewpoint of the heat resistance of the substrate, it is preferably 120° C. or less, and more preferably 100° C. or less.

[0055] <Annealing treatment (heat treatment) method> After the conductive layer is formed, an annealing treatment is performed. The temperature in the annealing treatment is preferably 85 to 130° C., and more preferably 95 to 125° C. Within the above numerical range, deterioration of the performance of the piezoelectric film is easily prevented, and high transparency and low resistance tend to be achieved.

[0056] In particular, the transparent conductive piezoelectric laminate film according to the present invention can be produced by a production method including the steps of: (A) forming a conductive layer on at least one surface of a transparent piezoelectric film containing a fluorine-based resin to obtain a laminate film; and (B) annealing the laminate film obtained in the above step (A) at 85 to 130°C. In the above step (A), before forming the conductive layer, it is preferable to form a transparent coating layer on the surface of the transparent piezoelectric film on which the conductive layer is to be formed, and then form the conductive layer on the transparent coating layer. EXAMPLES

[0057] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these examples. The properties of the transparent conductive piezoelectric laminate film of the present invention were measured by the following methods, and the results are shown in Table 1.

[0058] [Surface resistance] The surface resistance of each transparent conductive piezoelectric laminate film was measured from the conductive layer side using Loresta GP (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with JIS K 7194.

[0059] [Total light transmittance] The total light transmittance of each transparent conductive piezoelectric laminate film was measured using a haze meter ("NDH7000SP II", manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7361-1.

[0060] [Haze value] In accordance with JIS K 7136, the haze value of each transparent conductive piezoelectric laminate film was measured using a haze meter ("NDH7000SP II", manufactured by Nippon Denshoku Industries Co., Ltd.).

[0061] [Color measurement] Each transparent conductive piezoelectric laminate film was measured using a spectrophotometer ("SE7700", manufactured by Nippon Denshoku Industries Co., Ltd.) according to a method in accordance with JIS Z 8722.

[0062] [Adhesion] The adhesion of each transparent conductive piezoelectric laminate film was evaluated by a cross-cut method. On the conductive layer of each transparent conductive piezoelectric laminate film, 11 lines were cut vertically and horizontally at 1 mm intervals with a cutter to create 100 grids, and then tape (Nichiban Co., Ltd.'s Cellotape (registered trademark), adhesive strength 4.01 N / 10 mm) was applied and peeled off, and the proportion of the conductive layer that peeled off from the piezoelectric film was evaluated according to the following criteria in accordance with ASTM D3359. 0B: 65% or more peeling 1B: Peeling of 35% or more and less than 65% 2B: Peeling of 15% or more and less than 35% 3B: Peeling of 5% or more and less than 15% 4B: Less than 5% peeling 5B: No peeling

[0063] [X-ray diffraction measurement (XRD)] Using an X-ray diffractometer, the diffraction angle (2θ) range of 15.0 to 70.0° was scanned at a scanning speed of 1° / min, and measurements were performed by the in-plane method. Details of the measurement conditions are shown below. The measurement results of Examples 1 and 2 and Comparative Example 1 are shown in Figures 3 to 5, respectively. For each of the ranges of 21°±2° and 31°±2°, the presence of a diffraction peak is indicated by ◯, and the absence of a diffraction peak is indicated by ×. In addition, the diffraction intensity (cps) of the diffraction peak is also shown when a diffraction peak is present.

[0064] <Measurement conditions> Equipment: Rigaku SmartLab X-ray source: Cu-Kα (λ=1.5418Å) 40kV 30mA Detector: SC-70 Step width: 0.04° Scan range: 15.0~70.0° Slit: Entrance slit = 0.2 mm Length control slit = 10mm Receiving slit = 20 mm

[0065] [Examples 1 to 4 and Comparative Examples 1 to 3] A resin film (width 350 mm, thickness 120 μm) made of polyvinylidene fluoride (manufactured by Kureha Corporation) with an inherent viscosity of 1.10 dl / g was uniaxially stretched to a stretch ratio of 4.2 times. After stretching, the film was passed through a polarizing roll to perform a polarization treatment, and a piezoelectric film was obtained. At that time, the polarization treatment was performed by applying a DC voltage that was increased from 0 kV to 12.0 kV. The film after the polarization treatment was further heat-treated at 130°C for 1 minute to obtain a transparent piezoelectric film with a thickness of 40 μm. An ultraviolet-curable resin composition containing amorphous silica (average particle size 80 nm) was applied to one surface (first main surface) of the transparent piezoelectric film using a bar coater and dried at 80°C for 2 minutes. The dried coating film was irradiated with 400 mJ / cm using a UV irradiation device CSOT-40 (manufactured by GS Yuasa Corporation). 2 The other side was subjected to the same procedure to obtain a film having a first transparent coating layer and a second transparent coating layer with a thickness of 1.0 μm on both sides. A 40 nm thick conductive layer was formed on the first transparent coating layer by reactive sputtering using a sintered material containing indium oxide, hafnium oxide, and tantalum oxide as a target (Comparative Example 1). This was heat-treated at a predetermined temperature for 180 minutes to obtain a transparent conductive piezoelectric laminate film (Examples 1 to 4, Comparative Examples 2 and 3). Note that for Comparative Example 3, the film itself was deformed, making evaluation difficult, so X-ray diffraction measurement could not be performed.

[0066] Example 5 In the same manner as in Examples 1 to 4 and Comparative Examples 1 to 3, a transparent piezoelectric film having a thickness of 40 μm was obtained. A conductive layer having a thickness of 40 nm was formed on one surface (first main surface) of the transparent piezoelectric film by reactive sputtering using a sintered material containing indium oxide, hafnium oxide, and tantalum oxide as a target. This was heat-treated at 100°C for 180 minutes to obtain a transparent conductive piezoelectric laminate film (Example 5).

[0067] [Table 1]

[0068] As shown in Table 1, the examples had low surface resistance, high total light transmittance, low haze value, and high brightness. Therefore, it was confirmed that the present invention can provide a transparent conductive piezoelectric laminate film that achieves high transparency and low resistance. [Explanation of symbols]

[0069] 1, 2: transparent conductive piezoelectric laminate film, 11: piezoelectric film, 21: first transparent coating layer, 31: conductive layer

Claims

1. The piezoelectric film has a conductive layer laminated on at least one surface of the piezoelectric film. the conductive layer contains indium or an indium compound, and tantalum oxide and / or hafnium oxide; In X-ray diffraction measurement using Cu-Kα (λ=1.5418 Å) as an X-ray source, the crystal has diffraction peaks in the 2θ ranges of 21°±2° and 31°±2°, A transparent conductive piezoelectric laminate film having a haze value of 2.0% or less.

2. A transparent conductive piezoelectric laminate film as described in claim 1, wherein the conductive layer does not contain tin or tin compounds.

3. A transparent conductive piezoelectric laminate film as described in claim 1, wherein the intensity of the diffraction peak in the 2θ range of 21°±2° is greater than or equal to the intensity of the diffraction peak in the range of 31°±2°.

4. 2. The transparent conductive piezoelectric laminate film according to claim 1, wherein the surface resistance measured from the conductive layer side is 200 Ω / sq or less.

5. A transparent conductive piezoelectric laminate film as described in claim 1, wherein the conductive layer consists solely of indium oxide, hafnium oxide, and tantalum oxide.

6. The transparent conductive piezoelectric laminate film according to claim 1 , further comprising a transparent coating layer on a surface of the piezoelectric film facing the conductive layer.

7. A device comprising the transparent conductive piezoelectric laminate film according to any one of claims 1 to 6.

8. (A) forming a conductive layer on at least one surface of a transparent piezoelectric film containing a fluorine-based resin to obtain a laminated film; The method for producing a transparent conductive piezoelectric laminate film according to any one of claims 1 to 6, further comprising: (B) a step of annealing the laminate film obtained in the step (A) at 85 to 130°C.

9. 9. The method for producing a transparent conductive piezoelectric laminate film according to claim 8, wherein in step (A), before forming the conductive layer, a transparent coating layer is formed on a surface of the transparent piezoelectric film on which the conductive layer is to be formed, and the conductive layer is formed on the transparent coating layer.

Citation Information

Patent Citations

  • Electrostatic capacity type touch panel

    JP1993324203A

  • Pressing-detection device and touch panel

    WO2014185530A1

  • Piezoelectric film

    WO2015064328A1

  • Bimorph-type piezoelectric film

    WO2015129829A1

  • Piezoelectric film and piezoelectric sensor

    WO2019102635A1